Primer registro de un caso de malformaciones en lithobates neovolcanicus (hillis & frost 1985) (anura: ranidae) - Barragán-Ramírez, José Luis; Navarrete-Heredia, José Luis (Instituto de Ecología, A.C., 2011)
On September 9th, 2010, we found an individual of Lithobates neovolcanicus in a pond near to a disturbed pine forest from Mezcala de la Asunción, Poncitlán, Jalisco. The specimen presented two different deformities in its left forelimb and right hindlimb, polymelia and ectromelia, respectively. This is the first record of limb malformations in this endemic Mexican species.